STRATEGI PEMBERDAYAAN MAStrategi Pemberdayaan Masyarakat Nelayan di Desa Margasari Lampung TimurSYARAKAT NELAYAN DI DESA MARGASARI LAMPUNG TIMUR - Valentina, Annissa; Wardany, Kusuma (Journal of Nonformal Education and Community Empowerment, 2020)
The purpose of this study was to determine the empowerment of fishing communities in the implementation of empowerment activities in Margasari Village, East Lampung. The activity of empowering coastal fishing communities is a learning process in the context of increasing the capacity of the main players and business actors in the marine and fisheries sector to organize themselves in developing the fisheries business to increase their income and welfare while still paying attention to the preservation of environmental functions. The community plays a very important role in empowering the economy, so that it aims to improve the quality of life of the fishing community, meaning that through the participation that is given, it means truly realizing that development activities are not just an obligation that must be carried out by the government but also demand community involvement which will improve the quality of life. This research is a field research. The research method used in this research is a qualitative approach with sampling techniques through purposive sampling. Data collection techniques used interviews as the main method, observation and documentation as a complementary method. Analysis of data using qualitative analysis with data conclusions using inductive methods. The results show that it was found that 86.4% of the community did not understand empowerment programs, and 4.5% understood empowerment programs.